Exploitation of resistance to trypanosomes and trypanosomosis - D'Ieteren, G.D.M.; Authié, Edith; Wissocq, N.M.; Murray, M. (CAB International, 2000)
While an increasing number of examples of innate resistance to disease are being identified in domestic livestock, resistance to the effect of trypanosomes is one of the best-recognized and most thoroughly investigated. Experimental and field studies reviewed in this chapter are providing the basic tools with which the trypanotolerance trait can be identified and exploited. Comprehensive evaluation of the degree of genetic determination of the different disease resistance traits, their heritability and their genetic correlations with each other and with animal performance traits should allow progress to be made in the Development of breeding programmes and policies. There is increasing recognition that Africa possesses animal genetic resources probably unparalleled in any other continent. Evidence that these resources can provide sustainable and environmentally sound solutions for some of the vast disease problems currently confronting Africa is now being found. Thus, the natural innate resistance possessed by breeds of cattle, such as the N'Dama and the West Africa Shorthorn, to trypanosomosis and to several other important infectious diseases is now accepted as an important component of national and regional disease-control programmes. The fact that these breeds also possess considerable production potential and that their disease-resistance traits could be exploited in crossbreeding offers an unparalleled opportunity to improve livestock production in the vast areas of Africa dominated by the tsetse fly, ticks and helminths, particularly as more market-oriented production evolves. Topics of discussion includes major hindrance to sustainability of livestock production in the tropics; trypanosomosis control; trypanotolerance - a major asset for sustainable livestock production under trypanosomosis risk; biology of trypanotolerance; exploitation of trypanotolerance traits; and multiple attributes of trypanotolerant livestock.